2023
DOI: 10.3389/fphar.2023.1162995
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell death-related lncRNA signature as a predictive factor of clinical outcomes and immune checkpoints in gastric cancer

Abstract: Background: Immune cell death (ICD) is a type of tumor cell death that has recently been shown to activate and regulate tumor immunity. However, the role of ICD-related long non-coding RNAs (lncRNAs) in gastric cancer remains to be clarified.Methods: We obtained 375 tumor samples from the Cancer Genome Atlas (TCGA) database and randomly assigned them to training and verification groups. LASSO and Cox regression analysis were utilized to identify ICD-related lncRNAs and establish a risk model. The changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For this reason, a bioinformatics analysis was carried out in this research in order to identify novel biomarkers that could contribute to early diagnosis. Tsvetkov et al recently revealed a brand-new mechanism of cell death (cuprotosis), which is completely different from the existing cell death mechanism, as well as has great application potential in tumor therapy [7,24,25]. LncRNAs were particularly attractive candidates, given their well-established role in cellular differentiation, growth and development, and their documented association with aberrant expression patterns in various diseases, including malignancies [26].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a bioinformatics analysis was carried out in this research in order to identify novel biomarkers that could contribute to early diagnosis. Tsvetkov et al recently revealed a brand-new mechanism of cell death (cuprotosis), which is completely different from the existing cell death mechanism, as well as has great application potential in tumor therapy [7,24,25]. LncRNAs were particularly attractive candidates, given their well-established role in cellular differentiation, growth and development, and their documented association with aberrant expression patterns in various diseases, including malignancies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, cuproptosis, and necroptosis are all important cell death modalities that play an important role in the tumor microenvironment ( Shen et al, 2022 ; Xie et al, 2022 ; Zhang et al, 2023 ). It was found that ferroptosis could be involved in tumorigenesis, progression, and activation of different regulatory sites in the ferroptosis pathway and could promote tumor cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of RNA molecules that, while not coding for proteins, have been increasingly recognized for their pivotal roles in regulating gene expression, cellular processes, and pathways ( Zhang et al, 2023 ). Aberrant expression of lncRNAs has been implicated in cancer initiation, progression, and metastasis, marking them as potential diagnostic markers and therapeutic targets ( Peng et al, 2023 ).…”
Section: Ion-induced Cuproptosis In Cancermentioning
confidence: 99%